Gamification in internal marketing : Interactive work environment as productivity booster - Kuusijärvi, Juho (My University, 2020)
Enhancing workforce productivity has fascinated organizations for ages. To find more effective measures to improve customer experience as well as to reduce idle time. This is also the case for the case company, as they want to reduce the amount of idle time from their workforce. As gamification has been an effective asset in productivity increasing in other industries, studying gamification within business environment may unearth new knowledge in the ways of performance increasing. Not only this, but as insurance industry is not considered as an interesting workplace by millennials, gamification´s interactive characteristics may solve this recruitment issue as well. However, as gamification is only a part of the bigger picture, it needs aid from another concept focused on communication and creating knowledge for the gamification to utilize – internal marketing. The purpose of this thesis was to discover gamified internal marketing´s ability to improve work performance by motivating and engaging employees through gamified internal marketing processes and by gamifying their everyday activities. Another purpose was to show the case company their current situation within their customer service department and how well the employees understand the goals and the vision of the company. In order to attain these purposes, a literature review was conducted in order to find out more about the two concepts and commonalities within them, that could allow them to be combined to create the new concept of gamified internal marketing, presented as a theoretical framework. Based on the requirements, the research questions were made and with them, semi-structured in-depth interviews. Qualitative approach allowed the thesis to find deep information about the interviewee’s insights of motivation, recompensing and department´s situation. The findings indicated that internal marketing can be gamified, and that gamified internal marketing can boost productivity. Gamification as well as gamified internal marketing can be applied within the department’s work environment.

Työtehokkuuden kasvattaminen on kiinnostanut organisaatioita jo kauan, jotta asiakaskokemusta saataisiin parannettua ja passiivista työntekoa vähennettyä. Tämä on myös tavoitteena tapausyrityksessä, joka tahtoo vähentää passiivista työntekoa organisaatiossaan. Koska pelillistäminen on todettu tehokkaaksi työkaluksi muilla aloilla, sen tutkiminen liiketoimintaympäristössä voi tuoda esille uutta tietoa toiminnan tehostamiseksi. Tämän lisäksi milleniaalit eivät koe vakuutusalan työtehtäviä mielenkiintoisiksi, joten pelillistämisen interaktiiviset piirteet voivat ratkaista myös työnhakuhaastetta. On kuitenkin otettava huomioon, että pelillistäminen vaatii tuekseen kommunikaatioon ja tiedonkeruuseen erikoistuneen käsitteen – sisäisen markkinoinnin. Tutkimuksen tavoitteena oli saada selville pelillistetyn sisäisen markkinoinnin kyky kehittää organisaation työntekijöiden työtehokkuutta motivoimalla ja innostamalla työntekijöitä pelillistetyn sisäisen markkinoinnin prosesseilla ja pelillistämällä päivittäisiä työtehtäviä. Toisena tavoitteena oli osoittaa case-yritykselle heidän tämänhetkinen tilanteensa asiakaspalveluyksikössä ja kuinka onnistuneesti organisaation toimintasuunnitelma on työntekijöillä tiedossa. Jotta näihin tavoitteisiin päästäisiin, kirjallisuuskatsaus suoritettiin tiedonkeruuta varten, jotta käsitteistä ja niiden yhtymäkohdista saisi tarvittavat tiedot pelillistetyn sisäisen markkinoinnin teoreettisen viitekehyksen tekoon. Tätä varten muodostettiin tutkimuskysymykset ja niiden avulla luotiin puolistrukturoitu haastattelurunko. Kvalitatiivinen tutkimustapa valittiin, jotta haastateltavilta saatua tietoa motivaatiosta, palkitsemisesta ja osaston tilanteesta voitaisiin tutkia syvällisesti. Löydökset osoittavat, että sisäinen markkinointi voidaan pelillistää, ja pelillistetyllä sisäisellä markkinoinnilla voidaan luoda ja kasvattaa motivaatiota, jonka kautta työtehokkuutta saadaan tehostettua. Löydösten mukaan pelillistämisen sekä pelillistetyn sisäisen markkinoinnin implementointi osastolle on mahdollista
Keywords: gamification, internal marketing, motivation, recompensing, workforce productivity